A Study on Removal of Styphnic Acid in Aquatic Environment by Using UV-H2O2/nano TiO2 - Manh Khai, Nguyen; Van Huong, Nguyen; Thi Ngoc Anh, Nguyen; Duc Loi, Vu (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4313, 2018)
Abstract: The research focused on survey application capability of optical catalyst nano TiO2 foroxidationstyphnic acid (TNR) in wastewater by UV-H 2 O 2 . The affect of reaction conditions including times (0-90 minute), pH, wavelength of UV, molar ratios H 2 O 2 /TiO 2 , temperature, initial concentration on removal efficiencis of TNR were examined. Consequenceof C TNR = 154,4 mg/L, molar ratios as H 2 O 2 /TiO 2 = 15, pH=3 and wavelength UV= 313nm resulting 100% TNR was treated after 90 minute reaction. The temperatures in ranged of 30-50 o C were not significantly effectedthe TNR removal efficiency. Keywords : TNR, axit stynic, UV- H 2 O 2 , nano TiO 2 , removal. References [1] Đỗ Bình Minh (2015), Nghiên cứu đặc điểm quá trình chuyển hóa trong môi trường nước của các hợp chất nitrophenol trong một số hệ oxy hóa nâng cao kết hợp bức xạ UV, Luận án Tiến sĩ Hóa học, Viện Khoa học và Công nghệ quân sự. [2] Do Ngoc Khue, Nguyen Van Chat, Do Binh Minh (2013), Degradation and mineralization of 2,4,6-trinitroresorcine in various photochemical systems, Materials Science and Engineering, P. 1975-1982 [3] Meng Nan Chong, et al. (2010), Recent developments in photocatalytic water treatment technology: A review, Water research, 44, 2997- 3027. [4] Keiichi Tanaka, et al. (1997), Photocatalytic degradation of mono-, di- and trinitrophenol in aqueous TiO2suspension, Journal of Molecular Catalysis A: Chemical 122, 67-74. [5] Manoj A. Lazar, et al. (2012), Photocatalytic water treatment by titanium dioxide: Recent update, Catalysts, 2, 572 - 601. [6] Munter Rein (2001). Advanced oxidation processes–current status and prospects. Proceedings of the estonian academy of sciences. Chemistry. 50 (2): 59–80.